2013
DOI: 10.5792/ksrr.2013.25.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Two Techniques for Ligament Balancing in Total Knee Arthroplasty for Severe Varus Knee: Medial Soft Tissue Release vs. Bony Resection of Proximal Medial Tibia

Abstract: PurposeBony resection of the proximal medial tibia, an alternative technique for soft tissue balancing in total knee arthroplasty (TKA), was compared to the conventional medial soft tissue release technique.Materials and MethodsFrom June 2005 to June 2007, we performed 40 TKA in 27 patients with ≥10° tibio-femoral varus deformity. The conventional, medial soft tissue release technique was applied in 20 cases and bony resection of proximal medial tibia in the other 20 cases (vertical osteotomy group). Total ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 16 publications
1
31
0
Order By: Relevance
“…By applying the novel stepwise release technique to our patients with severe varus deformity, there was a concern as to whether other procedures beyond the three-step release technique would balance the deformity. Some surgeons recommended proximal tibial osteotomy as the final step of the procedure in patients with severe varus deformity [13,15]. We agree that an additional osteotomy can be performed for the knees with a combined severe varus angulation and bony deformity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By applying the novel stepwise release technique to our patients with severe varus deformity, there was a concern as to whether other procedures beyond the three-step release technique would balance the deformity. Some surgeons recommended proximal tibial osteotomy as the final step of the procedure in patients with severe varus deformity [13,15]. We agree that an additional osteotomy can be performed for the knees with a combined severe varus angulation and bony deformity.…”
Section: Discussionmentioning
confidence: 99%
“…Mullaji et al [13] described more complicated balancing techniques, including sequential releases of dMCL, semimembranosus, posteromedial capsule, and pes anserinus, tibia reduction osteotomy, and extra-articular correction. In addition to the above mentioned studies, various and complex protocols of medial release have been reported [15][16][17][18][19]. Somewhat extensive release techniques can lead to complications such as instability and neurovascular injury [12].…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The importance of proper tensioning of the collateral ligaments for the clinical success of total knee arthroplasty (TKA) has been comprehensively established. 1,5,35 A number of different methods for intraoperative ligament balancing have been introduced, targeting tension balance in the medial and lateral collateral ligaments (MCL and LCL) at full extension as well as at 90°of knee flexion. 12,33,35 However, the optimal ligament tension (or indeed laxity), during TKA is generally judged based on subjective manual evaluation by the surgeon rather than quantitative metrics.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, this is associated with downsizing of the tibial tray. The utilization of the MTRO may result in a decrease in operative times when compared to soft tissue releases alone [10] and typically lessens the amount of medial soft tissue releasing required to correct the varus deformity. Additionally, aggressive medial soft tissue release can lead to attenuation of the medial collateral ligament [11] (MCL).…”
Section: Introductionmentioning
confidence: 99%